Asian Literary Voices From Marginal to Mainstream - Williams, Philip F. (ICAS Publications Series, 2010)
Brings together some of the most exciting recent scholarship on Asian literature and culture, emphasising East Asia yet extending to South Asia Combines original findings of interest to specialists with a clear style of writing and argumentation that makes the volume accessible and appealing to the general reader Brings to life a wide range of Asian literary and scholarly figures important in their time and remain relevant and yet whose significance has been poorly understood